Teaching Learning English through Hasya Rasa - Budhathoki, Mahendra Kumar (Education and Development, 2020)
Language classes should be interesting and enjoyable to learn language effortlessly; learners should learn language without stress and burden in learning process. This article aims to describe rasa theory as a teaching method in language classroom. The research has occupied qualitative descriptive textual method; it is a library research. Language learning should be fun and stress free. The selected humorous poems and jokes make memorization of vocabulary items and their usages easy. The short-situational plot and dialogues make learning and memorization natural. Jokes and humorous poems help to learn language stress-freely. It becomes more effective for the learners of about six to twelve years and the beginners. This article describes only ‘hasya rasa’ among other ‘rasas’ in rasa theory. Teaching-learning English through (hasya) rasa theory is a unique and interesting method in ELT. This article provides ELT practitioners with the insight to explore more about the implication of rasa theory into ELT.